The Development of Student Worksheet Based on Guided Inquiry in Environmental Pollution Submaterial to Pratice Creative Thinking Skill for 10Th Grade of Senior High School - Putri, Larasati Hening; Ibrahim, Muslimin (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
The purpose of this research is to develop environmetal pollution student worksheet based on guided inquiry to practice creative thinking skills that are valid, practical, and effective,. The development of LKPD uses the 4-D method namely Define, Design, Develop, without applying the Disseminate phase. The trial was conducted on 20 students of class X MIPA 5 SMAN 1 Waru Sidoarjo by using a pretest-posttest design. Validity is obtained through validation by education experts and material experts. The practicality of worksheet is measured based on the assessment of the feasibility of learning while using LKPD. The effectiveness of worksheet is measured based on learning outcomes along with student responses after learning using worksheet. Data validity, practicality, and effectiveness analyzed by descriptive quantitative method. The results of research trials show the modus category of validity of LKPD is very valid. The practicality of LKPD is 100% with a very practical category. The effectiveness based on the results of students' creative thinking has increased until 88% with the category of very creative on 4 aspects of creative thinking and based on student responses of 95,42% with very effective category. Keywords: Validity, practicality, effectiveness, student worksheet, guided inquiry, creative thinking skill.